Learning styles and courseware design - Karen Valley (Association for Learning Technology, 1997)
As the use of technology to support teaching and learning becomes more widespread, the need to make learning with computers more effective becomes more important. The accommodation of individual learning styles is often regarded as a way of increasing learning effectiveness. The idea that we can classify a learner and then employ methods and activities that match the way they prefer to learn is an attractive one. The main goal of this paper is to examine how software for teaching and learning (courseware) can accommodate differences in preferred learning style.